2013
DOI: 10.1002/anie.201308175
|View full text |Cite
|
Sign up to set email alerts
|

A d10 Ni–(H2) Adduct as an Intermediate in HH Oxidative Addition across a NiB Bond

Abstract: Bifunctional EH activation offers a promising approach for the design of two‐electron‐reduction catalysts with late first‐row metals, such as Ni. To this end, we have been pursuing H2 activation reactions at late‐metal boratranes and herein describe a diphosphine–borane‐supported Ni—(H2) complex, [(PhDPBiPr)Ni(H2)], which has been characterized in solution. 1H NMR spectroscopy confirms the presence of an intact H2 ligand. A range of data, including electronic‐structure calculations, suggests a d10 configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
129
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(135 citation statements)
references
References 37 publications
5
129
1
Order By: Relevance
“…These dual effects should both further stabilize η 2 -H 2 binding in M−LA relative to the case of a single metal center, M [32]. As a practical consequence, employing Lewis acidic Group 13 metal ions as supports for a transition metal have led to the discovery and isolation of rare η 2 -H 2 adducts of d 10 Ni(0) [38,39]. To date we have not isolated any η 2 -H 2 adducts of M A M B L where M B is a transition metal, and so orbital interactions with H 2 will not be considered here for the case of a supporting transition metal.…”
Section: 1mentioning
confidence: 99%
“…These dual effects should both further stabilize η 2 -H 2 binding in M−LA relative to the case of a single metal center, M [32]. As a practical consequence, employing Lewis acidic Group 13 metal ions as supports for a transition metal have led to the discovery and isolation of rare η 2 -H 2 adducts of d 10 Ni(0) [38,39]. To date we have not isolated any η 2 -H 2 adducts of M A M B L where M B is a transition metal, and so orbital interactions with H 2 will not be considered here for the case of a supporting transition metal.…”
Section: 1mentioning
confidence: 99%
“…[3] Within this area, the vast majority of the research has focused on borane Lewis acids, [4] and has relied upon ambiphilic ligands to stabilize metal-borane interactions, since unsupported metal-borane compounds have thus far evaded isolation.…”
mentioning
confidence: 99%
“…Peters et al have also reported the synthesis of [Ni(N 2 )( iPr DPB Ph )] ( iPr DPB Ph = {o-( i Pr 2 P)C 6 H 4 } 2 BPh), which crystallized with three independent molecules within the unit cell, two of which are [Ni(N 2 )( iPr DPB Ph )] and one of which is [{Ni-( iPr DPB Ph )} 2 (μ-N 2 )]. Similarly to 4, the nickel center in the dimetallic compound is pseudotetrahedral with Ni−N and N− N bond lengths of 1.920 and 1.123 Å, respectively 17. The N N stretching frequency in 4 is 2006 cm −1 , which is shifted to lower frequency relative to the aforementioned [{Ni-(PP R P)} 2 (μ-N 2 )] complexes (ν(NN) = 2045 cm −1 (R = Me) and 2038 cm −1 (R = OMe)).…”
mentioning
confidence: 98%